2013
DOI: 10.3109/09540261.2013.769939
|View full text |Cite
|
Sign up to set email alerts
|

The overlap of symptomatic dimensions between frontotemporal dementia and several psychiatric disorders that appear in late adulthood

Abstract: Several factors make diagnosis of a possible behavioural variant of frontotemporal dementia (bvFTD) particularly challenging, especially the overlap of certain symptomatic dimensions such as apathy, disinhibition, depression, anhedonia, stereotyped behaviour, and psychosis between bvFTD and several psychiatric disorders that appear in late adulthood. We discuss the most frequent psychiatric conditions that can simulate early bvFTD symptoms, including late onset bipolar disorder, late onset schizophrenia-like p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 99 publications
0
48
1
3
Order By: Relevance
“…Clinical evaluation is crucial, but clinicians encounter an overlap of symptoms between bvFTD, psychiatric affective disorders and AD [6]. For this reason, the clinical evaluation must be completed with imaging markers.…”
Section: Diagnosis Of Bvftd Patientsmentioning
confidence: 99%
“…Clinical evaluation is crucial, but clinicians encounter an overlap of symptoms between bvFTD, psychiatric affective disorders and AD [6]. For this reason, the clinical evaluation must be completed with imaging markers.…”
Section: Diagnosis Of Bvftd Patientsmentioning
confidence: 99%
“…bvFTD has a broad differential diagnosis of both neurodegenerative and psychiatric disorders, resulting in a similar late-onset behavioral syndrome [4,5,6,7,8,9,10,11,12,13]. Although biomarkers take a prominent position in the present FTDC criteria, it is still unclear how they can distinguish between bvFTD and a representative control group [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews have suggested some "red flags" that should raise suspicions for an FTD diagnosis, including cognitive dysfunction, in particular aphasia or executive dysfunction, lack of distress in the setting of mood or anxiety disorders, progressive impairment, lack of treatment response, and unusual psychiatric features, such as compulsions without obsessions, sustained manic states without grandiosity or euphoria, or schizophrenia without complex delusions or hallucinations. 8,24 These criteria seem reasonable and are relevant to some of our cases, for instance, Case 1 who showed lack of distress and compulsions without obsessions. Cases 2-4 appear to have been more typical, and the sensitivity of these criteria may not have been adequate to identify them in the earliest phases of illness.…”
Section: Discussionmentioning
confidence: 99%